2019
DOI: 10.3390/su12010186
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fiscal Subsidies on the Sustainability of China’s Rural Pension Program

Abstract: This paper studies the impact of fiscal subsidies on the sustainability of China’s rural pension system. We first provide an overview of China’s rural pension system, and explain the formulas used to calculate the pension payments. We then examine how fiscal subsidies, in the forms of basic pensions, incentive pensions, and matching subsidies, affect participation rates and individual contributions. Our study shows that the rural residents’ participation rates can be improved significantly by increasing basic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The issues of aging population, poverty and participation behavior of pension plans are prevalent in many rural areas, especially in some developing countries (Lin and Zhang, 2019). Scholars and policy makers recognize the effect after implementing the NRPP .…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The issues of aging population, poverty and participation behavior of pension plans are prevalent in many rural areas, especially in some developing countries (Lin and Zhang, 2019). Scholars and policy makers recognize the effect after implementing the NRPP .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Families with higher income levels will pay more for the NRRP. In this regard, the burden of family pension and the pressure of education expenditure also restrict the probability of participating in the NRRP and contribution plans (Lin et al, 2018;Lin and Zhang, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…By the end of 2021, the NRPS participation rate exceeds 91% nationwide, and rural residents account for more than 90% [7]. The implementation of NPRS has been effective in alleviating health opportunity inequalities between urban and rural elderly [7], improving the quality of retirement for rural elderly [8], and improving the well-being of rural elderly [9,10]. However, most participants selected the lowest all annual contribution level [9,10], which may limit the extent of NPRS in improving life quality of rural elderly [11][12][13], which is an important issue in the Chinese economy [14].…”
Section: Introductionmentioning
confidence: 99%
“…The budget balance of the basic endowment insurance fund has been the focus of academic attention for a long time. Up to now, there have been lots of relevant researches in academic fields, when Lin and Zhang studied the sustainability of financial subsidies to pensions, they found that financial subsidies of pension insurance can significantly increase the participation rate and individual contributions, thereby improving the solvency of the fund [3]. While few studies combining the contribution rate, collection responsibility transformation, and the solvency of pension fund.…”
Section: Introductionmentioning
confidence: 99%